An update on bacterial brain abscess in immunocompetent patients. (September 2017) - Sonneville, R.; Ruimy, R.; Benzonana, N.; Riffaud, L.; Carsin, A.; Tadié, J.-M.; Piau, C.; Revest, M.; Tattevin, P.
Abstract: Background: A brain abscess is a focal infection of the brain that begins as a localized area of cerebritis. In immunocompetent patients, bacteria are responsible for >95% of brain abscesses, and enter the brain either through contiguous spread following otitis, sinusitis, neurosurgery, or cranial trauma, or through haematogenous dissemination. Aims: To identify recent advances in the field. Sources: We searched Medline and Embase for articles published during years 2012–2016, with the keywords 'brain' and 'abscess'. Content: The triad of headache, fever and focal neurological deficit is complete in ∼20% of patients on admission. Brain imaging with contrast—preferentially magnetic resonance imaging—is the reference standard for diagnosis, and should be followed by stereotactic aspiration of at least one lesion, before the start of any antimicrobials. Efforts should be made for optimal management of brain abscess samples, for reliable microbiological documentation. Empirical treatment should cover oral streptococci (including milleri group), methicillin-susceptible staphylococci, anaerobes and Enterobacteriaceae . As brain abscesses are frequently polymicrobial, de-escalation based on microbiological results is safe only when aspiration samples have been processed optimally, or when primary diagnosis is endocarditis. Otherwise, many experts advocate for anaerobes coverage even with no documentation, given the sub-optimal sensitivity of current techniques. A 6-week combination of third-generation cephalosporin and metronidazole will cure most cases of community-acquired brain abscess in immunocompetent patients. Implications: Significant advances in brain imaging, minimally invasive neurosurgery, molecular biology and antibacterial agents have dramatically improved the prognosis of brain abscess in immunocompetent patients over the last decades.